(untitled) (Journal of Science and Technology, 2015)
Liriodenine an oxoaoorphine and discretine a tetrahydroprotoberberine isolated from the stem bark of Pachypodanthium staudtii and characterised by physicochemical data. The Plant, Pachypodanthitum staudtii is a tropical annonaceous plant found in the closed evergreen forest from Sierra Leone to Zaire. The bark especially is claimed to have medicinal properties and is so used in folk medicine. The Chemotaxonomic significance of the isolated alkaloids and the medicinal importance of liridonine in relation to the folk-loric use of the plant are discussed.